A review of two-step sintering for ceramics. Issue 11 (15th August 2016) - Lóh, N.J.; Simão, L.; Faller, C.A.; De Noni, A.; Montedo, O.R.K.
Abstract: The development of high-density ceramic materials with fine-grained microstructures has been studied to considerably improve their properties for high-performance applications. Many alternatives have been searched to refine their microstructure by changing their composition and/or processing. Among such alternatives, the densification of ceramic materials by sintering curve control is an effective, simple and economical microstructure refinement method. Thus, different thermal treatment techniques such as spark plasma sintering and microstructural forms of control such as the control of sintering conditions have been used to obtain nanostructured materials. One of the techniques widely used in recent years is two-step sintering. Two-step sintering (TSS) is a promising method used to obtain high-density bodies and smaller grain sizes. Two TSS methodologies are known: sintering with thermal pretreatment at a low sintering temperature, followed by a second stage at elevated temperature, and the more recent approach presented by Chen and Wang, which has been the most widely used. In addition to the sintering conditions (temperature, heating rate and sintering holding times) that must be suitable for each composition type, the starting materials, particle size and processing method may influence the obtained microstructure, especially the reduced grain size and increased densification. The current review of two-step sintering presents the effect of this technique on the grain density and sizes of different ceramic materials. The influence of the addition of doping agents and its effect on the mechanical properties in different systems is also presented in the current study.